ヌルメイケ ノ 2ソウ コウゾウ ニ ツイテ - 佐野, 方昴; サノ, マサタカ; 中井, 信之; ナカイ, ノブユキ; 鳥居, 鉄也; トリイ, テツヤ; SANO, Masataka; NAKAI, Nobuyuki; TORII, Tetsuya (国立極地研究所, 1977)
P(論文) 南極ラングホブデ地区,ぬるめ池の主要溶存塩類の鉛直分布から,同池は,水深約10mを境にして,海水とほぼ同じ主要溶存塩類濃度の上層と,海水濃度の約1.5倍の下層からなっていることが見出された.この2層構造の成因を考察し,主要溶存塩類の濃度,組成,地理的条件から,下層は,湖水が濃縮して形成され,その後,海水の流入によって上層が生成されたという過程が推定された. It was found that Lake Nurume has the structure composed of two water layers differing in chemical composition. Concentrations of major dissolved components in the upper layer are nearly the same as those of sea water and the lower layer has 1.5 times greater major ion concentration than sea water. Formation of this two-layer structure can be ascribed to the following processes. The major ion concentration and chemical composition of the pond water and the geographical position of Lake Nurume, suggest that the lower layer was made by concentration of the original pond water which was sea water in the past, and then sea water flowed into the pond to make the upper layer. departmental bulletin paper